Red and processed meat and pancreatic cancer risk: a meta-analysis - Sun, Yudi; He, Xinyi; Sun, Yan (Frontiers in Nutrition, 2023)
The relationship between red and processed meat consumption and pancreatic cancer risk is controversial and no study has looked specifically at the correlation for six years. We conducted a meta-analysis to summarize the evidence about the association between them. Methods: We systematically searched PubMed, Embase and Cochrane Library for studies of red or processed meat consumption and pancreatic cancer published from December 2016 to July 2022. We performed random-effects models to pool the relative risks from individual studies. Subgroup analyses were used to figure out heterogeneity. We also performed publication bias analysis. Results: Seven cohort studies and one case-control study that contained a total of 7,158 pancreatic cancer cases from 805,177 participants were eligible for inclusion. The combined RRs (95% CI) comparing highest and lowest categories were 1.07 (95% CI: 0.91-1.26; P=0.064) for red meat and 1.04 (95% CI: 0.81-1.33; P=0.006) for processed meat with statistically significant heterogeneity.This meta-analysis suggested that red and processed meat consumption has no relationship with pancreatic cancer risk.